A framework for the evaluation of research in South African Higher Education Institutions : conceptual and methodological issues - Masipa, Mochaki Deborah (Stellenbosch : University of Stellenbosch, 2011)
Thesis (PhD (Social Science Research Methodology))--University of Stellenbosch, 2011.